Respuesta :

First 

y(x + -3) = 4y + -12\

Then you would 
Reorder the terms:
y(-3 + x) = 4y + -12 (-3 * y + x * y) = 4y + -12
 
And theses 
(xy + -3y) = 4y + -12(xy + -3y) = 4y + -12

then we would 
Reorder the terms:xy + -3y = -12 + 4y

then you would 
Move all terms containing x to the left, all other terms to the right.

so that means we would 
Add '3y' to each side of the equation.xy + -3y + 3y = -12 + 4y + 3y

then you would want to 
Combine like terms: -3y + 3y = 0xy + 0 = -12 + 4y + 3y xy = -12 + 4y + 3y
Combine these two 4y + 3y = 7yxy = -12 + 7y
then we would want to Divide each side by 'y'.x = -12y-1 + 7

so after simplifying it, it would be 
x = 7 + -12y-1


remember yuo can do anything to an equaiton as long as you do it to both sides


(x-3)=4y-12
x-3=4y-12
add 12 both sides
x-3+12=4y+12-12
x+9=4y+0
x+9=4y
divid both sides by 4
(x+9)/4=y
ACCESS MORE